A Guided Digital Interaction Digital Parenting Strategy for Early Childhood Cognitive Development among Working Mothers - Pria Dita Anis Wari; Dewi Eko Wati; Muqowim Muqowim; Khamim Zarkasih Putro; Noviarti Noviarti; Febriyanti Aulia Maulida; Siska Herna Putri (Universitas Islam negeri Mahmud Yunus Batusangkar, 2026)
Digital exposure in early childhood has become an increasingly significant factor influencing cognitive development, particularly in attention, memory, and information processing. In this context, parental mediation plays a critical role in shaping how children interact with digital devices. This study aims to explore how Guided Digital Interaction is implemented as a digital parenting strategy by working mothers to support early childhood cognitive development. This qualitative case study involved working mothers from various professional backgrounds, including teachers, midwives, and notary clerks. Data were collected through in-depth interviews and non-participant observations, and analyzed using the Miles and Huberman interactive model. The findings show that effective digital parenting is not determined by the amount of time mothers spend physically with their children, but by the quality of mediated interaction. Five key dimensions of Guided Digital Interaction were identified: proactive technological adaptation, transforming digital media into learning tools through reflective discussion, active co-engagement in digital activities, dialogic communication to encourage reasoning, and consistent environmental regulation. These strategies function as scaffolding that shifts children from passive digital consumption to active cognitive engagement. The study concludes that structured and interactive digital mediation can serve as an effective parenting strategy to support cognitive development and build cognitive resilience in early childhood, particularly among working mothers managing dual roles.